2016
DOI: 10.3390/e18020052
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Entropy Generation in Nanofluid Flow inside a Channel by Response Surface Methodology

Abstract: Nanofluids can afford excellent thermal performance and have a major role in energy conservation aspect. In this paper, a sensitivity analysis has been performed by using response surface methodology to calculate the effects of nanoparticles on the entropy generation. For this purpose, the laminar forced convection of Al 2 O 3 -water nanofluid flow inside a channel is considered. The total entropy generation rates consist of the entropy generation rates due to heat transfer and friction loss are calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…They perceived that entropy generation near the channel wall rapidly increased with the increase of the joule heating parameter. A few remarkable contributions on entropy generation with diverse studies can be explored in References [22][23][24][25][26][27][28].The existing literature firmly endorses that the effective influences of electro-magnetohydrodynamics (EMHD) and entropy generation with nanoparticles through a wavy channel on Poiseuille flow synthesis, are yet not to be addressed. In addition, what made this investigation more fruitful was to observe the simultaneous application of electro-hydrodynamics (EHD) and thermal radiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They perceived that entropy generation near the channel wall rapidly increased with the increase of the joule heating parameter. A few remarkable contributions on entropy generation with diverse studies can be explored in References [22][23][24][25][26][27][28].The existing literature firmly endorses that the effective influences of electro-magnetohydrodynamics (EMHD) and entropy generation with nanoparticles through a wavy channel on Poiseuille flow synthesis, are yet not to be addressed. In addition, what made this investigation more fruitful was to observe the simultaneous application of electro-hydrodynamics (EHD) and thermal radiation.…”
mentioning
confidence: 99%
“…They perceived that entropy generation near the channel wall rapidly increased with the increase of the joule heating parameter. A few remarkable contributions on entropy generation with diverse studies can be explored in References [22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…Darbari et al used the response surface method (RSM) to conduct a numerical sensitivity analysis of the effect of nanoparticles (Al 2 O 3 ) in water-based nanofluids on EG [9]. The results indicated that the total EG comprised EG due to friction and due to heat conduction.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the frictional entropy generation enhances as the Darcy number decreases. Darbari et al performed entropy generation analysis for nanofluid flow through a channel. They concluded that the total entropy generation reduces with an increase in the nanoparticles diameter.…”
Section: Introductionmentioning
confidence: 99%